2019
DOI: 10.3390/membranes9070083
|View full text |Cite
|
Sign up to set email alerts
|

Composite Membranes for High Temperature PEM Fuel Cells and Electrolysers: A Critical Review

Abstract: Polymer electrolyte membrane (PEM) fuel cells and electrolysers offer efficient use and production of hydrogen for emission-free transport and sustainable energy systems. Perfluorosulfonic acid (PFSA) membranes like Nafion® and Aquivion® are the state-of-the-art PEMs, but there is a need to increase the operating temperature to improve mass transport, avoid catalyst poisoning and electrode flooding, increase efficiency, and reduce the cost and complexity of the system. However, PSFAs-based membranes exhibit lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
90
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(91 citation statements)
references
References 206 publications
(237 reference statements)
1
90
0
Order By: Relevance
“…Due to this, symmetrical devices composed of pseudocapacitive materials are not favourable for high energy capacity EES devices and various asymmetrical designs have been proposed to achieve high voltage. Currently, two main designs for asymmetrical devices exist in which one involves asymmetrical supercapacitors with positive and negative electrodes (the positrode: the positive electrode [24,27,[38][39][40][41][42][43]; the negatrode: the negative electrode [24,27,[39][40][41][42][43][44]) capable of capacitive charge storage typically through the permutation and combination of EDL and pseudocapacitive electrodes, whereas the other design involves hybrid configurations that combine supercapacitor electrodes with battery electrodes and have been reported under different names that mainly correspond to the different electrode materials used. Overall, the word 'hybrid' is not a suitable unified expression for the future development of these asymmetrical devices because it is too abstract, whereas the terms 'supercapattery' or 'supercabattery' are general enough to represent Fig.…”
Section: Fundamentals Of Supercapatteriesmentioning
confidence: 99%
“…Due to this, symmetrical devices composed of pseudocapacitive materials are not favourable for high energy capacity EES devices and various asymmetrical designs have been proposed to achieve high voltage. Currently, two main designs for asymmetrical devices exist in which one involves asymmetrical supercapacitors with positive and negative electrodes (the positrode: the positive electrode [24,27,[38][39][40][41][42][43]; the negatrode: the negative electrode [24,27,[39][40][41][42][43][44]) capable of capacitive charge storage typically through the permutation and combination of EDL and pseudocapacitive electrodes, whereas the other design involves hybrid configurations that combine supercapacitor electrodes with battery electrodes and have been reported under different names that mainly correspond to the different electrode materials used. Overall, the word 'hybrid' is not a suitable unified expression for the future development of these asymmetrical devices because it is too abstract, whereas the terms 'supercapattery' or 'supercabattery' are general enough to represent Fig.…”
Section: Fundamentals Of Supercapatteriesmentioning
confidence: 99%
“…This requirement has led to limiting PEMFC operating temperature to 80 • C as operation above that will lead to dehydration of the membrane and a subsequent loss in proton conductivity and fuel cell performance. However, PEMFC operating above 80 • C can benefit from increased reaction kinetics, reduced CO poisoning and simplified water and thermal management [29]. One method utilised to allow that transition into intermediate temperatures is the use of filler materials within the polymer [30].…”
Section: A Short Review On Pfsas (Nafion Polymers)mentioning
confidence: 99%
“…The introduction of some of these inorganics like metal/metal oxides, carbon‐based nanomaterials, nanoclays, and solid proton conductors (eg, heteropolyacids, super‐acids, and layered metal phosphates) into the SPEEK polymer matrix and their effects were extensively studied. Metal oxide nanomaterials are more promising fillers that have recently attracted an increasing research interest toward fuel cell applications because of their hygroscopic nature besides the proton conductivity of acidic sites . In addition, diminishing of fuel crossover and enhancing of the mechanical and thermal strength has been adequately satisfied by modification of these nanomaterials .…”
Section: Introductionmentioning
confidence: 99%
“…Metal oxide nanomaterials are more promising fillers that have recently attracted an increasing research interest toward fuel cell applications because of their hygroscopic nature besides the proton conductivity of acidic sites. 24 In addition, diminishing of fuel crossover and enhancing of the mechanical and thermal strength has been adequately satisfied by modification of these nanomaterials. 25 For instance, Sigwadi et al impregnated a ZrO 2 -CNT nanoparticle into a Nafion polymer matrix 26 and found that the mechanical properties and water retention of the nanocomposite membrane was enhanced compared with the plain Nafion 117.…”
Section: Introductionmentioning
confidence: 99%